Patient perspectives in the face of climate change: improving maternal and child health outcomes through patient-centered design - Muhammad, Ameer (Journal of the Pakistan Medical Association, 2023)
Dear Editor, The impact of climate change on maternal, newborn, and child health in Pakistan is profound. Further, the country is susceptible to extreme weather conditions, such as floods, heatwaves, and droughts, which could disrupt healthcare services, damage healthcare infrastructure, and increase disease risks. These impacts are expected to worsen in the coming years. Food systems can be disrupted by changing temperatures, precipitation patterns, and other climate-related factors, resulting in disease outbreaks, natural disasters, and other health problems.1 The patient-centered design process involves incorporating community perspectives into health interventions and engaging communities in the design process. Consequently, interventions can be more culturally appropriate, acceptable, and feasible, which will ensure their long-term success. Patient-centered design can also promote equity and inclusion, which are critical to addressing these complex and interrelated health challenges. Poverty, lack of access to healthcare, gender inequalities, and poverty often hinder the health of mothers, newborns, and children and reduce these barriers can be addressed by incorporating the perspectives and experiences of patients into health interventions and putting them at the center of the design process. Consequently, more effective, equitable, and sustainable health systems can be developed that are better suited to address climate change’s complex health challenges.2 Here are a few examples of how patient-centered design can be integrated in maternal and child health services to combat the effects of climate change: Climate-resilient infrastructure: Incorporating features into healthcare such as reinforced roofing, raised floors, and backup generators are all examples of measures that can be used to prevent medical facilities from being affected by climate change.3 Access to safe water and adequate sanitation: In areas affected by climate change, safe water and adequate sanitation can play a major role in preventing disease and improving health.3 Patient-centered clinic design: The utilization of maternal and child health services can be increased by providing features such as private consultation rooms and comfortable waiting areas.4 Health education and awareness: Communities can build resilience and reduce negative health impacts by providing health education and awareness, especially in climate-affected areas.5 Incorporating patient-centered design into maternal and child health services can increase health service utilization and improve quality of care. As a result, the healthcare system can be more resilient and effective to climate change challenges.